2011
DOI: 10.1002/elan.201100577
|View full text |Cite
|
Sign up to set email alerts
|

Application of Modified Tafel Analysis to the Identification of Corrosion Products on Archaeological Metals Using Voltammetry of Microparticles

Abstract: An operational modification of Tafel analysis, applied to the intermediate region of square wave voltammetric curves, devoted to the identification of corrosion products on archaeological metal, is described. This is based on the voltammetry of microparticles methodology using conventional abrasive conditioning of the electrode, as well as one-touch and layer-by-layer techniques. The proposed methodology is applied to the identification of copper and silver corrosion products in mediaeval silver-copper coins f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 71 publications
5
39
0
1
Order By: Relevance
“…Electrochemical methods were very popular for metal conservation for most of the XX century, but were progressively abandoned in the 1970s-1980s due to the changes in the conservation-restoration criteria [9]. However, developments in the application of electrochemical techniques in the last 20 years have made them popular again for metallic cultural heritage, as conservation treatment [10][11][12], for analytical purposes [13][14][15][16] or to evaluate the efficiency of other conservation-restoration treatments [9,[17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Electrochemical methods were very popular for metal conservation for most of the XX century, but were progressively abandoned in the 1970s-1980s due to the changes in the conservation-restoration criteria [9]. However, developments in the application of electrochemical techniques in the last 20 years have made them popular again for metallic cultural heritage, as conservation treatment [10][11][12], for analytical purposes [13][14][15][16] or to evaluate the efficiency of other conservation-restoration treatments [9,[17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…In short, the idea is that the initial rising portion (at the foot of the peak) of the voltammetric peaks can be approached by an exponential relationship between the current and the applied potential. Since the measured current at a given potential (and, in particular, the peak current) will depend on the amount of solid transferred onto the electrode surface, it is convenient to use the generalized current, defi ned as the current/peak current ratio, which satisfi es [105,106]:…”
Section: Composition Of Corrosion Productsmentioning
confidence: 99%
“…Published by Woodhead Publishing Limited, 2013 parameters can be complemented with those obtained from the Tafel analysis of voltammetric peaks [65,102,105,106], which is of particular interest for discerning between corrosion products displaying quite similar voltammetric responses [30]. In short, the idea is that the initial rising portion (at the foot of the peak) of the voltammetric peaks can be approached by an exponential relationship between the current and the applied potential.…”
Section: Composition Of Corrosion Productsmentioning
confidence: 99%
“…The VMP has been applied to the identification of organic and inorganic pigments, ceramic, glass and glazed materials, fibers and hybrid pigmenting systems, as summarized in extensive reviews and textbook [2,27,28]. Although VMP has been used recently to identify corrosion products in copper/bronze [29][30][31][32][33], lead [34] and silver [35], no VMP studies specifically dealing with iron corrosion products have been reported.…”
Section: Introductionmentioning
confidence: 99%